A New Photovoltaic Emulator Designed for Testing Low-Power Inverters Connected to the LV Grid - Przemysław Korasiak; Janusz Jaglarz (Energies, 2022)
Assessing the performance of photovoltaic systems, particularly dedicated DC/AC inverter devices, requires the use of photovoltaic panels operating under natural environmental conditions, such as variations in solar radiation intensity, temperature and wind speed. Environmental testing is obviously very troublesome, inconvenient and limited. An alternative solution is to use a device that emulates the output photovoltaic panel curves in variable weather conditions, which allows the carrying out of all necessary tests at the laboratory. This paper presents a new photovoltaic emulator (PVE), mimicking the output characteristics of the photovoltaic panels. The proposed PVE is designed and constructed at the renewable energy laboratory for testing low-power PV inverters connected to the LV grid. A novelty of this solution is the method for shaping emulated current–voltage characteristics I–V. The concept of this method assumes autonomous regulation of slopes and shapes of emulated curve fragments. This allows us to obtain the desired shapes of the output characteristics for a wide range of both voltages and currents. The proposed PVE is not a pulse device; it belongs to linear analogue circuits. In order to confirm the assumed concept, a prototype is designed and constructed, and laboratory tests are conducted. Satisfactory results are obtained, confirming the correctness of the adopted concept. High compliance of the emulated characteristics is found in comparison to the characteristics of the selected commercial photovoltaic module. Very good results of dynamic tests and energy efficiency measurements are achieved.